2014
DOI: 10.1097/scs.0000000000001168
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Arthrocentesis for the Treatment of Internal Derangement Pain

Abstract: The AC is an effective procedure for a short-term reduction of pain in temporomandibular disorder cases. It seems that AC using Ringer solution with or without corticosteroids may have the same effect on pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
1
19
0
10
Order By: Relevance
“…The full texts of these articles were gathered and each one fulfilled the inclusion criteria were observed. Relying on the Jadad scale ( Table 2 ), three studies had a score of 5 ( 20 - 22 ), two had a score of 4 ( 23 , 24 ), and two had a score of 3 ( 13 , 17 ), for a total of 7 high quality studies. The rests, which had low Jadad scale, were excluded from the study to avoid biases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full texts of these articles were gathered and each one fulfilled the inclusion criteria were observed. Relying on the Jadad scale ( Table 2 ), three studies had a score of 5 ( 20 - 22 ), two had a score of 4 ( 23 , 24 ), and two had a score of 3 ( 13 , 17 ), for a total of 7 high quality studies. The rests, which had low Jadad scale, were excluded from the study to avoid biases.…”
Section: Resultsmentioning
confidence: 99%
“…The initial literature search yielded on 2067 articles (Cochrane Library=45/ Web of Science=5/ Google Scholar=1390/ PubMed=47/ ProQuest=107/ Scopus=473), in which 1402 articles remained after removing duplicates. After the first screening based on the title and abstract, 11 studies ( 13 , 16 , 17 , 20 - 27 ) were found eligible which reached to 7 studies ( 13 , 17 , 20 - 24 ) after excluding high risk articles (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The question becomes whether TMJ arthralgia is caused by an inflammation triggered by IA agents, which is diluted at the IA intervention, or whether the nerve block anaesthetic stops a windup phenomenon. In addition, in arthrocentesis studies in which the intervention procedure was completed with or without deposition of corticosteroids for treatment of TMJ arthralgia, arthrosis and internal derangement have no significant effects on pain intensity . Thus, it seems obvious that the combination of procedures, local anaesthetic and injected fluid reduce TMJ pain.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies with different follow-up periods have shown that a single arthrocentesis procedure results in a decrease in pain ranging from 37 to 86%. 3,31,36,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] These studies generally involve heterogeneous populations and most inject HA or CS as part of the procedure. These studies are not double blinded and most are not randomized, which introduces potential bias and confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusion: Arthrocentesis alone is as efficacious as arthrocentesis with HA or CS in decreasing TMJ pain. Ó 2016 American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg 75: [52][53][54][55][56][57][58][59][60][61][62]2017 Temporomandibular joint (TMJ) dysfunction (TMD) is a heterogeneous group of disorders characterized by the presence of facial pain and limited jaw function. The etiology is often multifactorial and, accordingly, many different treatments exist.…”
mentioning
confidence: 99%